Criminal Law Functionalization in Overcoming Post-Extraction Dental Commercialization (Universitas PGRI Madiun, 2022)
The commercialization of organs and body tissues is regulated in Article 64 Paragraph (3) of Law Number 36 Year 2009 concerning Health. Violation of these provisions can be punished under Article 192. Post-extraction teeth can be used for the practice of dental students. Certain parties to get teeth from the dentist’s practice for sale use this opportunity. The problem in this research is how to functionalize criminal law in tackling the commercialization of post-extraction teeth. This research used socio legal approach. To answer the problems used primary data and secondary data. Primary data was obtained by conducting interviews with medical students and dentists. Secondary data obtained from document study. Data were analyzed qualitatively. The research shows that the functionalization of the commercialization of post-extraction teeth is still in the formulation stage. There is no criminal application against the perpetrators of this crime